The Effectiveness Of Habits Of Mind Training Program On Jordanian Gifted Students’ Creative Thinking And Problem Solving Skills - M. Ewies, Mahmoud Ghazi (2022)
Gifted students are the wealth of any country, so it is necessary for this group of students to have creative thinking skills and problem-solving ability. This research aimed to study the effectiveness of Habits of Mind training program on Jordanian gifted students’ creative thinking and problem-Solving skills. Descriptive and mixed-mode design was used. A descriptive design was used to explain the use of the Habits of Mind training program. A mixed-mode design uses a quantitative approach (Quasi-experimental) and qualitative approach (Interviews). The study sample comprised eighty gifted students from King Abdullah II Schools of Excellence in Madaba Governorate in Jordan. The sample was chosen with a randomized stratified approach. The students were divided into two control and experimental groups.